Manajemen Pembelajaran Online dalam Meningkatkan Kemampuan Berkomunikasi Bahasa Inggris Mahasiswa - Arif Hidayat (Indo-MathEdu Intellectuals Journal, 2023)
The research stems from concerns among graduate students who lack proficiency in English communication, essential in today's era of global competition. This study aims to comprehensively analyze the online-based English language learning management's role in enhancing students' English communication skills. Specific objectives encompass English Learning Planning, Organizing, Implementation, and Evaluation, while addressing inhibiting factors and devised solutions. Employing the POAC management function (Planning, Organizing, Actuating, Controlling) by G.R. Terry, the research follows a qualitative case study approach. Outcomes demonstrate that effective planning with vision, mission, objectives, and schedules significantly improves students' English communication skills. Organizing online English learning through an optimized structure and dedicated teaching team facilitates the process. Curriculum-guided implementation utilizes native speaker guest lecturers for an enriched experience. Evaluations are consistently refined through iterative processes. Despite challenges such as human resources, infrastructure, and institutional policies, alternatives are established to overcome barriers. Solutions encompass human resources, facility enhancements, ICT advancements, and policy adaptations, all fostering English communication skills. Online-based English learning yields graduates with proficient English communication abilities, positively impacting their overall quality. However, the study highlights that the current online-based management hasn't reached its full potential in enhancing communication skills. Bridging the gap between online and practical learning can more effectively train students in English communication, gradually achieving the desired proficiency